The Neurogenic Compound P7C3 Regulates the Aerobic Glycolysis by Targeting Phosphoglycerate Kinase 1 in Glioma - Chen, Wenjin; Jia, Weiqiang; Wu, Cuiying; Chen, Lihua; Sun, Kai; Wang, Ji; Ding, Boyun; Liu, Ning; Xu, Ruxiang (Frontiers in Oncology, 2021)
Background: P7C3 is a neurogenic compound exhibits neuroprotective properties in neural cells. However, its target proteins and effects in glioma are unknown. Methods: The candidate P7C3 target proteins were analyzed using a human protein microarray containing 23136 human proteins. A streptavidin agarose affinity assay was used to verify the direct interaction between P7C3 and phosphoglycerate kinase 1 (PGK1). Mass spectrometry was used to identify the binding sites of PGK1 for P7C3 binding. Seahorse XF96 extracellular flux analyzer was used to measure the cell oxygen consumption rate and extracellular acidification rate. Glycolytic metabolites were measured using the related kits. Protein level was detected by western blotting and immunohistochemical staining. Autophagy was analyzed using transmission electron microscope and western blotting. The malignancy of tumor progression in vitro and in vivo was analyzed based on cell viability, apoptosis and proliferation, migration and invasion, and xenograft model. Glial cells were marked by antibodies via immunohistochemical staining. Results: The human protein microarray identified 577 candidate P7C3 target proteins. The global profile of P7C3 target proteins indicated that P7C3 regulates glycolysis. Metabolic experiments confirmed that P7C3 regulates aerobic glycolysis in glioma cells. The underlying mechanism of P7C3 was found to be direct targeting PGK1 at lysine residues and asparagine residues, and the specific P7C3-PGK1 interaction led to decreased protein level and total intracellular kinase activity of PGK1. The Cancer Genome Atlas and Chinese Glioma Genome Atlas databases indicated that mRNA level of PGK1 is significantly increased in high-grade glioma, and the abnormally high mRNA level of PGK1 is associated with a poor prognosis in patients with glioma, suggesting that PGK1 is a promising target for glioma therapy. The inhibition of PGK1 and the subsequent suppression aerobic glycolysis caused by P7C3 inhibited the malignant growth of glioma in vitro and in vivo. Furthermore, P7C3 did not damage normal glial cells under concentration which exhibit inhibitory effect on gliomas. Conclusions: This study revealed that P7C3 suppresses glioma by regulating aerobic glycolysis via directly targeting PGK1. Furthermore, we identified the P7C3 target proteins for the first time which is expected to provide scientific clues for future studies.